2008
DOI: 10.1007/s10157-008-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cystatin C in patients with malignancy

Abstract: The results of our study suggest that the serum levels of cystatin C are not always a reliable marker of the GFR in patients with a malignancy, probably in relation to its nature as a cysteine protease inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 21 publications
3
27
0
4
Order By: Relevance
“…No correlation was revealed in patients with progression, in whom cancer cells are the main source of Cyst C in serum. In these patients, the determination of cystatin C as GFR marker is not useful, which confirms Nakai's et al studies [9]. These authors found that serum levels of cystatin C were not always a reliable marker of renal efficiency in patients with a malignancy.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…No correlation was revealed in patients with progression, in whom cancer cells are the main source of Cyst C in serum. In these patients, the determination of cystatin C as GFR marker is not useful, which confirms Nakai's et al studies [9]. These authors found that serum levels of cystatin C were not always a reliable marker of renal efficiency in patients with a malignancy.…”
Section: Discussionsupporting
confidence: 72%
“…This protein is a member of the cystatin superfamily of cysteine protease inhibitors; the production rate of cystatin C is stable and does not change in inflammatory conditions [9]. Due to its nature, the serum level of cystatin C is known to be a better marker for GFR (glomerular filtration rate) than serum creatinine [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seksen iki renal fonksiyonları normal sınırlarda olan kanser tanılı hasta ile sağlıklı kontrol grubunun karşılaştırmalı çalışmasında ise kanser grubunda sistatin C düzeylerinin yüksek bulunduğu, bu nedenle kanserli hastalarda renal fonksiyonları göstermede iyi bir belirteç olamayacağı sonucuna varılmıştır (10).…”
Section: Introductionunclassified